Comparison of Real time PCR with traditional tools for diagnosis of Trichomonas vaginalis in patient with vaginal discharge at Kut city, Iraq - Rahi, Abdulsadah Abdulabbas; Ali, Magda A; Khamesipour, Ali (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Trichomoniasis is a sexually transmitted disease (STD) and most common form of STD which is caused by Trichomonas vaginalis. This is a descriptive analytical study. Vaginal swabs were collected from sixty female patients with suspected Trichomonas vaginalis infection aged 14-53 years old during September 2013 to March 2014 who attended the Gynecology Clinic of Kut city, Iraq. Two swabs were collected from each woman; one for wet mount microscopic examination and the other for Real Time PCR technique. Wet-mount microscopy were positive for T. vaginalis in 5/60 cases (8.33%) and positive Real-time PCR 13/60 (21.67%). The present study revealed that the highest incidence of T.vaginalis infection occurs in age group(24-33) years with the percentage of (46.1%). The sensitivity of Real-time PCR was 100% compared with 38.5% for wet-mount microscopy. The aim of the study was to compare a Real-time PCR assay with wet-mount examination for the detection of T. vaginalis.